Stress-Induced Reversion to Virulence of Infectious Pancreatic Necrosis Virus in Naïve Fry of Atlantic Salmon (Salmo salar L.) - Gadan, Koestan; Sandtrø, Ane; Marjara, Inderjit S.; Santi, Nina; Munang'andu, Hetron M.; Evensen, Øystein (PloS one, 2013)
We have studied stress-induced reversion to virulence of infectious pancreatic necrosis virus (IPNV) in persistently infected Atlantic salmon (Salmo salar L.) fry. Naïve fry were persistently infected with a virulent strain (T(217)A(221) of major structural virus protein 2, VP2) or a low virulent (T(217)T(221)) variant of IPNV. The fry were infected prior to immunocompetence as documented by lack of recombination activating gene-1, T-cell receptor and B-cell receptor mRNA expression at time of challenge. The fish were followed over 6 months and monitored monthly for presence of virus and viral genome mutations. No mutation was identified in the TA or TT group over the 6 months period post infection. Six months post infection TA and TT infected groups were subject to daily stress for 7 days and then sampled weekly for an additional period of 28 days post stress. Stress-responses were documented by down-regulation of mRNA expression of IFN-α1 and concomitant increase of replication levels of T(217)T(221) infected fish at day 1 post stress. By 28 days post stress a T221A reversion was found in 3 of 6 fish in the T(217)T(221) infected group. Sequencing of reverted isolates showed single nucleotide peaks on chromatograms for residue 221 for all three isolates and no mix of TA and TT strains. Replication fitness of reverted (TA) and non-reverted (TT) variants was studied in vitro under an antiviral state induced by recombinant IFN-α1. The T(217)A(221) reverted variant replicated to levels 23-fold higher than the T(217)T(221) strain in IFN-α1 treated cells. Finally, reverted TA strains were virulent when tested in an in vivo trial in susceptible salmon fry. In conclusion, these results indicate that stress plays a key role in viral replication in vivo and can facilitate conditions that will allow reversion from attenuated virus variants of IPNV.